Virtual potato crop modeling: A comparison of genetic coefficients of the DSSAT-SUBSTOR potato model with breeding goals for developing countries - Raymundo, R.; Kleinwechter, U.; Asseng, Senthold (2014)
Virtual crop modeling is the representation of future genetic improvements from plant breeding in crop growth simulation models through changes in genetic coefficients or other crop model parameters with the objective of analyzing ex-ante the impacts of improved traits on crop yields and assisting breeders in their breeding efforts.